Application of infrared spectroscopy for the prediction of nutritional content and quality assessment of faba bean (Vicia faba L.). Issue 3 (24th April 2020) - Johnson, Joel B.; Walsh, Kerry; Naiker, Mani
Abstract: With growing consumer interest and demand for health‐benefiting functional foods such as faba beans, particularly evident in developed countries, commercial production of this crop is increasing. In concert with increased production levels comes an equally great need for the inexpensive rapid measurement of nutritional parameters for quality determining purposes. As an analytical tool, near‐infrared spectroscopy has been well explored for the quantification of proximate nutritional composition, such as protein, starch and oil contents in faba bean and faba bean‐derived products. Near‐infrared spectroscopy has also been demonstrated to have potential for the noninvasive prediction of low‐level micronutrients such as the total polyphenol content in faba bean and faba bean‐derived products, although further exploration in this area is required to provide a more acceptable model. In some instances, the authors may be inadvertently measuring micronutrient concentrations through a secondary correlation with certain macronutrients. It is particularly difficult to determine if this is the case if exacerbated by the lack of an independent validation test set in the paper in question. The associated technique of mid‐infrared spectroscopy shows particular promise for the rapid, noninvasive characterisation of structural components of faba bean, such as carbohydrates and proteins. Complementary applications of these two technologies are likely to yield a wealth of potential applications.